Bulk pancreatic cancer cells can convert into cancer stem cells(CSCs) in vitro and 2 compounds can target these CSCs. Issue 3 (1st February 2016) - Ning, Xiaoyan; Du, Yiqi; Ben, Qiwen; Huang, Ling; He, Xiaoping; Gong, Yanfang; Gao, Jun; Wu, Hongyu; Man, Xiaohua; Jin, Jing; Xu, Ming; Li, Zhaoshen
ABSTRACT: Increasing evidence has confirmed the existence of cancer stem cells (CSCs) in both hematological malignancies and solid tumors. However, the origin of CSCs is still uncertain, and few agents have been capable of eliminating CSCs till now. The aim of this study was to investigate whether bulk pancreatic cancer cells could convert into CSCs under certain conditions and explore whether metformin and curcumin can kill pancreatic CSCs. Aspc1, Bxpc3 and Panc1 pancreatic cancer cells were cultured in stem cell culture medium (serum-free Dulbecco's modified Eagle medium/Nutrient Mixture F-12 containing basic fibroblast growth factor, epidermal growth factor, B27 and insulin) for 5 days and it was found that all the pancreatic cancer cells aggregated into spheres and expressed pancreatic cancer stem cell surface markers. Then characteristics of Panc1 sphere cells were analyzed and cytotoxicity assays were performed. The results show that Panc1 sphere cells exhibited CSC characteristics and were more resistant to conventional chemotherapy and more sensitive to metformin and curcumin than their parent cells. These findings suggested that bulk pancreatic cancer cells could acquire CSC characteristics under certain conditions, which may support the "yin-yang" model of CSCs (interconversion between bulk cancer cells and CSCs). These results also showed that metformin and curcumin could be candidate drugs for targeting pancreatic CSCs.